Molecular and comparative morphological analysis of central European parasitic flatworms of the superfamily Brachylaimoidea Allison, 1943 (Trematoda: Plagiorchiida) - Heneberg, Petr; Sitko, Jiljí; Bizos, Jiří (Parasitology, 2016)
The Brachylaimoidea are digenean parasites of vertebrates, including humans, domestic animals, poultry and wild game. Numerous Brachylaimoidea, particularly adults of Brachylaima and Leucochloridium, are difficult to identify to species. We provide and analyse sequences of two nuclear (18S rDNA, ITS2) and two mitochondrial (CO1, ND1) DNA loci of central European species of the Brachylaimoidea, namely Leucochloridium holostomum, Leucochloridium paradoxum, Leucochloridium perturbatum, Leucochloridium subtilis, Leucochloridium vogtianum, Urotocus rossitensis, Urogonimus macrostomus, Michajlovia migrata, Leucochloridiomorpha lutea, Brachylaima arcuatus, Brachylaima fuscata and Brachylaima mesostoma. We identified three clades in the genus Leucochloridium, which do not correspond to the previously suggested subgenera Neoleucochloridium, Papilloleucochloridium and Leucochloridium. We reject classification of Urotocus and Urogonimus in Leucochloridiinae, and, instead, re-establish the subfamilies Urotocinae and Urogoniminae. We synonymize the genus Renylaima with the genus Brachylaima. We reject M. migrata as a member of Leucochloridiinae sensu stricto or Brachylaimidae suggested by some previous authors. We found that the previously sequenced Glaphyrostomum sp. does not cluster with any hitherto sequenced Brachylaimidae. We also provide comparative measurements of the examined central European Brachylaimoidea, address the the specificity of their localization in the host and discuss their host-specific prevalence and intensity of infections based on the extensive dataset of birds examined in 1962-2015.
Keywords: Host Specificity; sekvenční seřazení; intestine; ptáci; bursa of Fabricius; RNA ribozomální 18S; DNA helmintů; Birds; DNA, Ribosomal; Phylogeny; mitochondriální DNA; DNA, Intergenic; prevalence; Trematoda; nemoci ptáků; Biological Evolution; DNA, Mitochondrial; Platyhelminthes; Trematode Infections; infekce červy třídy Trematoda; cloaca; DNA, Helminth; zvířata; Europe; hostitelská specificita; fylogeneze; biologická evoluce; zoonosis; ribozomální DNA; Prevalence; Animals; RNA, Ribosomal, 18S; Bird Diseases; intergenová DNA; Evropa; diarrhoea; Sequence Alignment